Transmisi Harga Beras di Indonesia: Pendekatan Threshold Cointegration - Deby Ananda Difah; Harianto Harianto; Dedi Budiman Hakim (Politeknik Negeri Lampung, 2019)
Rice is a staple food that is still a top priority for most of Indonesian. The widening difference between the rice price at the farmer level and the retail price of rice indicates the presence of asymmetric vertical price transmission. A stable and affordable price is one of the important components needed to maintain food distribution. The price of food commodities that fluctuate too much can be relied upon by farmers as producers, processors, traders to consumers, and about social unrest. To maintain stability of staple food prices, the government is open to keep rice prices at a certain level that can benefit farmers and consumers alike. This research used Threshold Vector Error Correction Model (TVECM) to estimate threshold value and to analyze rice price transmission relationship at farm level and retail level. The data used monthly time series data from January 1990 to September 2016. The results show that the estimated threshold value obtained is -0.092. This suggests that when the deviation of retail price and farmers in long-term equilibrium exceeds 9.2 percentage, the price of retail rice will adjust to achieve its equilibrium so that the two rice prices have a cointegration relationship. Conversely, when the deviation of rice prices is less than 9.2 percentage, there will be no price adjustment and no market integration. The price of retail rice has increased faster than the price at the farm level.Â Keywords: cointegration, price transmission, rice, threshold